Understanding Clostridium difficile Colonization - Monique J. T. Crobach; Jon J. Vernon; Vivian G. Loo; Ling Yuan Kong; Séverine Péchiné; Mark H. Wilcox; Ed J. Kuijper (2018)
Clostridium difficile is the main causative agent of antibiotic-associated and health care-associated infective diarrhea. Recently, there has been growing interest in alternative sources of C. difficile other than patients with Clostridium difficile infection (CDI) and the hospital environment. Notably, the role of C. difficile-colonized patients as a possible source of transmission has received attention. In this review, we present a comprehensive overview of the current understanding of C. difficile colonization. Findings from gut microbiota studies yield more insights into determinants that are important for acquiring or resisting colonization and progression to CDI. In discussions on the prevalence of C. difficile colonization among populations and its associated risk factors, colonized patients at hospital admission merit more attention, as findings from the literature have pointed to their role in both health care-associated transmission of C. difficile and a higher risk of progression to CDI once admitted. C. difficile colonization among patients at admission may have clinical implications, although further research is needed to identify if interventions are beneficial for preventing transmission or overcoming progression to CDI.